Production of Biochar Briquettes from Coconut Leaves - Heriyanti, Andhina Putri; Sultan, Habil; Rahmawati, Agustina Dwi; Tanjung, Jonathan Danosmon Maleakhi; Maharani, Saffira Alyda; Fariz, Trida Ridho (Journal of Environmental and Science Education, 2024)
Coconut leaf waste (Cocus nucifera), which contains various beneficial compounds, has not been utilized optimally by the community. Coconut leaves contain a valuable biomass of around 44,000 tonnes/ha to 67,000 tonnes/ha. This has the potential to be used as biochar. The research method used in this research is descriptive experimental research using coconut leaves as raw material for biochar briquettes using a pyrolysis carbonization process. This study used differences in the composition of starch which acts as an adhesive with 3 different variations, namely 2%, 4% and 6%. Based on the results of the ash content test and the calculation of the water content and density, the biochar briquettes in all samples complied with SNI 01/6235/2000.